2012
DOI: 10.1037/a0028290
|View full text |Cite
|
Sign up to set email alerts
|

Examining the validity of the family investment and stress models and relationship to children's school readiness across five cultural groups.

Abstract: Using the Early Childhood Longitudinal Study, Birth Cohort (ECLS-B) dataset, this study examined whether the family investment and the family stress models generalized to non-European American (EA) families. Specifically, we examined whether parenting processes mediated the association between family demographics and children's school readiness, and whether the pathways vary across cultural groups. Both models were most salient for EAs followed by African Americans (AAs) and Spanish-speaking Hispanics, but les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 65 publications
6
38
0
Order By: Relevance
“…In contrast, those parents who are warm and supportive, set consistent routines for their children, and provide more cognitively stimulating environments may facilitate their children's cognitive, behavioral, and academic development, even after accounting for SES and other sociodemographic characteristics (Iruka, LaForett, & Odom, 2012). Doing so may reduce the risk of having a limited vocabulary (Morgan et al, 2015).…”
Section: Importance Of Control For Confounding Factorsmentioning
confidence: 96%
“…In contrast, those parents who are warm and supportive, set consistent routines for their children, and provide more cognitively stimulating environments may facilitate their children's cognitive, behavioral, and academic development, even after accounting for SES and other sociodemographic characteristics (Iruka, LaForett, & Odom, 2012). Doing so may reduce the risk of having a limited vocabulary (Morgan et al, 2015).…”
Section: Importance Of Control For Confounding Factorsmentioning
confidence: 96%
“…Feldman and Masalha () attributed their finding that maternal sensitivity was predictive of Israeli Jewish, but not Palestinian, toddlers’ social competence to the view that greater emphases on hierarchy and compliance among Palestinian parents might have lessened the importance of mothers’ sensitivity for children's socialization. Another study that tested whether parental activities mediated the association between SES and preschoolers’ preacademic skills across ethnic groups found that parenting literacy practices might not be culturally relevant for non‐White parents (Iruka, LaForett, & Odom, ). Testing for moderation by ethnicity is important because European American values regarding rearing practices and parental investments tend to be different from those of Latino parents (Fuligni & Brooks‐Gunn, ).…”
Section: Moderation By Gender and Ethnicitymentioning
confidence: 99%
“…The MDoC Positive and Negative Affect scales also replicated past videotaped and observed measures of maternal affect in their associations with family demographics (Bradley, Corwyn, Pipes McAdoo, & Garcia Coll, 2001; Iruka, LaForett, & Odom, 2012; Lugo-Gil & Tamis-LeMonda, 2008), maternal mental health (Baker et al, 2000; Olino et al, 2011), and child behaviour (Callahan, Scaramella, Laird, & Sohr-Preston, 2011; Denham et al, 2000; Dennis, 2006). Further, the predictors of these scales resembled those of observed maternal affect scales in past studies.…”
Section: Discussionmentioning
confidence: 65%